Penerapan Perilaku Hidup Bersih Di Smk N 6 Kota Bengkulu - Siska, Jumiati; Rachayu , Imma; Yul , Fadlul Amdhi; Selviani , Diah; Fitrian , Yenni; Susanto , Edy; Luthfia , Izza (Jurnal Kewirausahaan dan Bisnis, 2021)
Based on the results of the activities and evaluation analysis, it can be concluded as follows The service material as an additional knowledge for students of SMKN 6 Bengkulu City that it turns out that the utilization and application of clean living is very important, the service participants are very enthusiastic about participating in the activities, which can increase knowledge which is very useful for students of SMKN 6 Bengkulu City. It is necessary to hold further community service with different materials so that students of SMKN 6 Bengkulu City are more motivated in practicing teaching skills in terms of utilizing other learning media.